Bibliometric analysis on the progress of immunotherapy in renal cell carcinoma from 2003-2022 - Haiyan Zhu; Xin Wang; Shihao Lu; Wu Jianqiang; Kongbo Ou; Na Li (Human Vaccines & Immunotherapeutics, 2023)
The incidence and mortality rates of renal cell carcinoma (RCC) have been increasing annually due to obesity and environmental pollution. Although immunotherapy of RCC has been studied for decades, few comprehensive bibliometric analyses exist on the treatment. Therefore, the purpose of this bibliometric analysis was to identify scientific achievements of the global research on RCC immunotherapy from 2003 to 2022 and discuss research trends. Data were retrieved from the Clarivate Web of Science Core Collection using a set retrieval strategy. The Bibliometrics tool Cite Space 6.2 R2 (Chaomei Chen, Drexel University) was used to analyze 4,841 articles. The USA had the most publications (n = 1,864); Harvard University was identified as the leading institution (n = 264); and Dr. Toni K. Choueiri, was the most productive researcher in the field (n = 55). Keyword analysis showed that nivolumab, immune checkpoint inhibitors, tumor microenvironment, everolimus, cabozantinib, resistance, pembrolizumab and ipilimumab were the main hotspots and frontier directions of RCC. By analyzing the results of bibliometrics, national and international researchers can better understand the current research status of RCC immunotherapy and identify new directions for future research. However, the analysis also identified pockets of insularity, highlighting a need for greater collaboration and cooperation among researchers to advance the field of RCC immunotherapy.